Evaluasi Pelayanan Kesehatan dan Pendidikan Program Keluarga Harapan - Restianti, Ayu (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2017)
This study seeks to a description the evaluation of health and education service of conditional cash transfers (Program Keluarga Harapan-PKH) based on an input, process, and output. It’s programme between 2016 until 2017 has been implemented in District of Jetis, Bantul. This paper demonstrates the results of the evaluation, though this results hoped input for the decision to programme repaired. This article, however, it seeks programme make good from health and education service component. Thus, I found Conditional Cash Transfers (CCT) or Progam Keluarga Harapan (PKH) programme have signed for even distribution of education and accessibility for health services on simply, particularly of pregnant wife and suckle. The importance of indicators at programme successfully, data validity has been doing of maximal. So, the candidate of participant didn’t perfunctorily in this programme. Hence, participatory of people (non-candidate) in this programme, also make good of indicators, which can be interdependent of control form another side. Eventually, the candidate of their programme, if not meet a demand just like the rule of manual books on 2016, they are can the punishment of exhortation, greeting, and defeasance of the programme. I also, however, found the weakness of tease enough, i.e. the beneficiary still considers that conditional cash transfer is only for a moment’s need, not thinking about long-term interests. In turn, the process of alleviating poverty is only 'patching the wound' rather than treating it to its problem needs.Studi ini berupaya mengkaji tentang evaluasi layanan kesehatan dan pendidikan Program Keluarga Harapan (PKH) berbasis input, proses pelaksanaan, dan output pada program yang sudah berjalan di Kec. Jetis, Bantul, dari tahun 2016 hingga 2017. Tujuan evaluasi yang telah dikaji, harapannya menjadi masukan bagi penentu kebijakan (decission) untuk memperbaiki program. Tulisan ini juga melihat keberhasilan program dari komponen layanan pendidikan dan kesehatan. Saya menemukan bahwa program Conditional Cash Transfers (CTT) atau PKH memiliki signifikansi nyata dalam pemerataan pendidikan dan akses yang mudah pada layanan kesehatan, terutama bagi ibu hamil dan menyusui. Indikator penting dalam keberhasilan program ini, validitas data berjalan secara maksimal, sehingga tidak asal dalam menentukan peserta penerima bantuan. Bukti keterlibatan masyarakat (non-peserta) dalam program juga menjadi indikator keberhasilan, sehingga bisa saling mengawasi antara satu sama lain. Alhasil, peserta yang tidak memenuhi kewajiban seperti aturan dalam buku pedoman 2016, mereka akan mendapat punishment mulai dari peringatan, teguran hingga pembatalan program bantuan. Namun saya juga menemukan kelemahan yang cukup mengusik, yaitu penerima manfaat masih menganggap bahwa bantuan langsung tunai bersyarat ini hanya untuk keperluan sesaat, tidak berpikir untuk kepentingan jangka panjang. Pada gilirannya, proses pengentasan kemiskinan hanya bersifat ‘menambal luka’ bukan mengobati hingga ke akar masalahnya (based needs).